GROSS MUNICIPAL PRODUCT IN ASSESSING THE LEVEL OF ECONOMIC DEVELOPMENT OF THE REPUBLIC OF SAKHA (YAKUTIA) - V. L. Pulyaevskaya; В. Л. Пуляевская (Novosibirsk State University of Economics and Management, 2016)
In this publication report presents the republic’s method of calculation of Gross Municipal Product by institutional sectors of economy broken down by 36 regions of the republic. The data presented in the report reflect the contribution of the regions to the formation of the republic’s GRP, give a generalized representation of functioning of the Sakha Republic’s economy broken down by economic activities and sectors of economy, and characterize the level of economic development. В статье предлагается республиканская методология расчета Валового муниципального продукта по институциональным секторам экономики в разрезе 36 районов республики. Данные, представленные в докладе, отражают вклад районов в формирование ВРП республики, дают обобщенное представление о функционировании экономики Республики Саха (Якутия) в разрезе видов экономической деятельности, секторов экономики и характеризуют уровень экономического развития.